Intersections of religion and astronomy - Ricker, Aaron; Corbally, Christopher J.; Dinnell, Darry (Routledge science and religion series, 2021)
"This volume examines the way in which cultural ideas about "the heavens" shape religious ideas and are shaped by them in return. Our approaches to cosmology have a profound effect on the way in which we each deal with religious questions and participate in the imaginative work of public and private world-building. Employing an interdisciplinary team of international scholars, each chapter shows how religion and cosmology interrelate and matter for real people. Historical and contemporary case studies are included to demonstrate the lived reality of a variety of faith traditions and their interactions with the cosmos. This breadth of scope allows readers to get a unique overview of how religion, science and our view of space have, and will continue to, impact our worldviews. Offering a comprehensive exploration of humanity and its relationship with cosmology, this book will be an important reference for scholars of Religion and Science, Religion and Culture, Interreligious Dialogue and Theology, as well as those interested in Science and Culture and Public Education"--